2019
DOI: 10.1007/s11606-019-05460-2
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of Drug Benefit in FDA-Approved Prescription Drug Labeling

Abstract: studies). Text, tables, and figures in each label's "Clinical Studies" section were independently evaluated by two authors, and disagreements were resolved through consensus with an additional author. For each indication, we extracted the primary efficacy outcome (either explicitly stated or implicitly defined) and recorded the presence or absence of the following attributes describing treatment effects for primary outcomes: point estimates, confidence intervals, and p values. Primary efficacy outcomes were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Others have documented a lack of varied understandings of noninferiority trials, including the trade-offs. 16 We also found that whether and how to explain a noninferiority trial in consent text eludes easy consensus. Ultimately, this confusion and concern might reflect that the noninferiority design is not an intuitive statistical or clinical concept, whereas superiority designs are likely more readily understandable or more familiar.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Others have documented a lack of varied understandings of noninferiority trials, including the trade-offs. 16 We also found that whether and how to explain a noninferiority trial in consent text eludes easy consensus. Ultimately, this confusion and concern might reflect that the noninferiority design is not an intuitive statistical or clinical concept, whereas superiority designs are likely more readily understandable or more familiar.…”
Section: Discussionmentioning
confidence: 79%
“…While there were concerns by stakeholders that patients might not understand the noninferiority concept, some investigators, study coordinators, and IRB members also had their own misconceptions. Others have documented a lack of varied understandings of noninferiority trials, including the trade-offs . We also found that whether and how to explain a noninferiority trial in consent text eludes easy consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Even the drug’s 17 page prescribing information for healthcare providers had little to say about the randomised trial results. In the section of the labelling where such efficacy data are typically presented,6 Recarbrio’s label offered the same information about the cUTI and cIAI studies, saying, “These trials provided only limited efficacy and safety information.”7…”
mentioning
confidence: 99%